Pengaruh Kinerja Makroekonomi Dalam dan Luar Negeri terhadap Penanaman Modal Asing di Indonesia - Juanda, Bambang; Mahyuddin, Mahyuddin (UI Scholars Hub, 2009)
This paper studies the effect of domestic and foreign macroeconomy performances on the foreign direct investment (PMA) in Indonesia, employing descriptive and inferencial (econometric model) analyses. The national economic grcwth and national interest rate affect significantly PMA in Indonesia. While the national inflation rate positively effected on PMA, but resuits show that hyperinflation contributes to decreasing PMA. The macroeconomic improvement in some competitor countries, especially Chinese and Thailand tends to decrease PMA in Indonesia. However, the improvement of macroeconomies in Singapore and Malaysia can increase PMA in Indonesia. Therefore, bilateral relationship with these countries must be intensified. In addition, although the economic growth of some More Developed Countries (MDCs) has positive relationship with PMA in Indonesia, but their effect were not significant statistically, except Canada. This implies that global finance crisis, especially in USA and european countries would not largely effect on PMA in Indonesia.